Body Size, Dispersal Potential, Range Size and Habitat Fragmentation Are Linked to Extinction Risk of Freshwater Mussels - Garrett W. Hopper; Sean M. Keogh; Carla L. Atkinson; Traci P. DuBose; Jeffrey D. Lozier; John M. Pfeiffer; Irene Sánchez González (Journal of Biogeography, 2026)
Aim Trait‐based approaches are increasingly recognised as tools for understanding species' vulnerabilities to intensifying global change. For species with complex life histories that involve a parasitic life stage, a combination of traits associated with either the host or parasite could influence extinction risk. Location United States of America. Taxon Freshwater mussels are a highly threatened assemblage of bivalves with an obligate ectoparasitic larval stage requiring a host fish. Adult mussels are sedentary, with long‐distance dispersal dictated by the dispersal ability of the host fish during the parasitic larval life phase. Methods We integrate several open‐source spatial and trait datasets for freshwater mussels and host fishes to test hypotheses about the relationship between species‐level traits such as body size, area of occupancy (AOO), host fish dispersal, habitat fragmentation and mussel extinction risk. Results Imperilled mussels were smaller, had smaller areas of occupancy, used small‐bodied, dispersal‐limited host fishes and had higher densities of large dams in their AOO compared to non‐imperilled mussels. Conclusions Body size, along with AOO and dispersal potential, appears to have cascading effects on imperilment where decreases in these traits potentiate population fragmentation via large dams. Thus, in contrast to many other groups, freshwater mussel body size is inversely related to extinction risk, and small‐bodied mussels should be closely monitored to prevent future extinctions.

Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Activation of the alternative complement pathway and its relevance for sodium retention in experimental nephrotic syndrome - Daniel Essigke; M. Zaher Kalo; Lingsi Kong; Matthias Wörn; Mohammad-Khaled Saad; Kingsley Omage; Bernhard N. Bohnert; Andreas L. Birkenfeld; John P. Atkinson; Xiaobo Wu; Ferruh Artunc (Pflügers Archiv - European Journal of Physiology, 2026)
The complement component C3, factor B (FB) and factor D (FD) belong to the alternative complement pathway and have been identified in urine samples from nephrotic mice. However, it is not yet known whether these factors are involved in mediating sodium retention in nephrotic syndrome (NS). Here we used a genetic mouse model of NS based on an inducible podocin deletion ( Nphs2 Δipod ). These mice were intercrossed with mice deficient for FB, FD or C3, yielding Nphs2 Δipod *Cfb −/− , Nphs2 Δipod *Cfd −/− or Nphs2 Δipod *C3 −/− mice, respectively. NS was induced after oral doxycycline treatment for 14 days. C3, FB and FD were detected in the nephrotic urine of Nphs2 Δipod mice as well as fragments of C3 and FB, indicating intrarenal activation of the alternative complement pathway. Lack of FB and FD had no impact on the activation of C3. Immunohistochemistry demonstrated positive C3 staining in protein casts and within the proximal tubule. Nephrotic mice of all genotypes experienced similar proteolytic activation of the epithelial sodium channel ENaC, developed sodium retention (urinary sodium concentration < 20 mM) and body weight gain. This was associated with a stimulation of proteolytic processing of epithelial sodium channel ENaC in all genotypes. In conclusion, components of the alternative complement pathway are detectable and activated in nephrotic syndrome. Mice with deletion of C3, FB or FD are not protected from proteolytic ENaC activation and sodium retention in NS.

An assessment model for linking changes in pelagic habitat state to impacts on human wellbeing - Matthew P. Faith; Siân E. Rees; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle J. Devlin; Matthew M. Holland; Holly J. Niner; Clare Ostle; Paul Tett; Abigail McQuatters-Gollop (Marine Policy, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Controls on regional sulphate distribution in shallow groundwater in the western Canadian Interior Plains - J.E. Liggett; K.E. Pooley; N. Atkinson; P. Humez; S. Thistle; B.D. Smerdon; M. Babakhani; C.N. McClain; B. Mayer (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Determinants of host breadth in non-native bark and ambrosia beetles - Soňa Šenfeldová; Thomas H. Atkinson; Miloš Knížek; Robert J. Rabaglia; Nathan P. Havill; Samuel F. Ward; Marek Turčáni; Andrew M. Liebhold (Forest Ecology and Management, 2024)

Relative sea‐level changes in southeastern Australia during the 19 th and 20 th centuries - S. L. Williams; E. Garrett; P. T. Moss; S. Dangendorf; F. D. Hibbert; N. R. Atkinson; V. Pashley; I. L. Millar; M. H. Garnett; A. Zawadzki; W. R. Gehrels (Journal of Quaternary Science, 2023)
Rates of global and regional sea‐level rise between ~1850 and 1950 were high compared to those in preceding centuries. The cause of this sea‐level acceleration remains uncertain, but it appears to be pronounced in a small set of relative sea‐level proxy records from the Southern Hemisphere. Here we generate three new proxy‐based relative sea‐level reconstructions for southeastern Australia to investigate spatial patterns and causes of historical sea‐level changes in the Tasman Sea. Palaeo sea‐level estimates were determined using salt‐marsh foraminifera as sea‐level indicators. Records are underpinned by chronologies based on accelerator mass spectrometry 14 C, radiogenic lead ( 210 Pb), stable lead isotopes and palynological analyses. Our reconstructions show that relative sea level rose by ~0.2–0.3 m over the last 200 years in southeastern Australia, and rates of sea‐level rise were especially high over the first half of the 20 th century. Based on modelled estimates of the contributing components to sea‐level rise, we suggest that the episode of rapid sea‐level rise was driven by barystatic contributions, but sterodynamic contributions were dominant by the mid‐20 th century. Significant spatial variability in relative sea level indicates that local to sub‐regional drivers of sea level are also prominent. Our reconstructions significantly enhance our understanding of the spatiotemporal pattern of early 20 th century sea‐level rise in the region.

Long-term exposure to traffic-related air pollution and stroke: A systematic review and meta-analysis - P. Haddad; M. Kutlar Joss; J. Weuve; D. Vienneau; R. Atkinson; J. Brook; H. Chang; F. Forastiere; G. Hoek; R. Kappeler; F. Lurmann; S. Sagiv; et al. (International Journal of Hygiene and Environmental Health, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

The development of visually guided stepping - Rachel Mowbray; Janna M. Gottwald; Manfei Zhao; Anthony P. Atkinson; Dorothy Cowie (Experimental Brain Research, 2019)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

Seismically induced landslide hazard and exposure modelling in Southern California based on the 1994 Northridge, California earthquake event - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Erratum to: Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2015)

A systematic review of landslide probability mapping using logistic regression - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2014)

Identification of a possible respiratory arsenate reductase in Denitrovibrio acetiphilus, a member of the phylum Deferribacteres - Kyle Denton; Morgan M. Atkinson; Stacey P. Borenstein; Alexis Carlson; Thomas Carroll; Kristen Cullity; Casey DeMarsico; Daniel Ellowitz; Andrea Gialtouridis; Rachel Gore; April Herleikson; Albee Yun Ling; et al. (Archives of Microbiology, 2013)

Analysing temporal trends in the Indian Summer Monsoon and its variability at a fine spatial resolution - J. M. A. Duncan; J. Dash; P. M. Atkinson (Climatic Change, 2013)

Environmental changes impacting Echinococcus transmission: research to support predictive surveillance and control - Jo‐An M. Atkinson; Darren J. Gray; Archie C.A. Clements; Tamsin S. Barnes; Donald P. McManus; Yu R. Yang (Global Change Biology, 2013)
Echinococcosis, resulting from infection with tapeworms Echinococcus granulosus and E. multilocularis, has a global distribution with 2–3 million people affected and 200,000 new cases diagnosed annually. Costs of treatment for humans and economic losses to the livestock industry have been estimated to exceed $2 billion. These figures are likely to be an underestimation given the challenges with its early detection and the lack of mandatory official reporting policies in most countries. Despite this global burden, echinococcosis remains a neglected zoonosis. The importance of environmental factors in influencing the transmission intensity and distribution of Echinococcus spp. is increasingly being recognized. With the advent of climate change and the influence of global population expansion, food insecurity and land‐use changes, questions about the potential impact of changing temperature, rainfall patterns, increasing urbanization, deforestation, grassland degradation and overgrazing on zoonotic disease transmission are being raised. This study is the first to comprehensively review how climate change and anthropogenic environmental factors contribute to the transmission of echinococcosis mediated by changes in animal population dynamics, spatial overlap of competent hosts and the creation of improved conditions for egg survival. We advocate rigorous scientific research to establish the causal link between specific environmental variables and echinococcosis in humans and the incorporation of environmental, animal and human data collection within a sentinel site surveillance network that will complement satellite remote‐sensing information. Identifying the environmental determinants of transmission risk to humans will be vital for the design of more accurate predictive models to guide cost‐effective pre‐emptive public health action against echinococcosis.

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Water velocity dependence of phosphate uptake on a coral-dominated fringing reef flat, La Réunion Island, Indian Ocean - P. Cuet; C. Pierret; E. Cordier; M. J. Atkinson (Coral Reefs, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Mapping the phenology of natural vegetation in India using a remote sensing-derived chlorophyll index - C. Jeganathan; J. Dash; P. M. Atkinson (International Journal of Remote Sensing, 2010)

On the seasonal cycles and variability of Florida Straits, Ekman and Sverdrup transports at 26° N in the Atlantic Ocean - C. P. Atkinson; H. L. Bryden; J. J-M. Hirschi; T. Kanzow (Ocean Science, 2010)
Since April 2004 the RAPID array has made continuous measurements of the Atlantic Meridional Overturning Circulation (AMOC) at 26° N. Two key components of this system are Ekman transport zonally integrated across 26° N and western boundary current transport in the Florida Straits. Whilst measurements of the AMOC as a whole are somewhat in their infancy, this study investigates what useful information can be extracted on the variability of the Ekman and Florida Straits transports using the decadal timeseries already available. Analysis is also presented for Sverdrup transports zonally integrated across 26° N. The seasonal cycles of Florida Straits, Ekman and Sverdrup transports are quantified at 26° N using harmonic analysis of annual and semi-annual constituents. Whilst Sverdrup transport shows clear semi-annual periodicity, calculations of seasonal Florida Straits and Ekman transports show substantial interannual variability due to contamination by variability at non-seasonal frequencies; the mean seasonal cycle for these transports only emerges from decadal length observations. The Florida Straits and Ekman mean seasonal cycles project on the AMOC with a combined peak-to-peak seasonal range of 3.5 Sv. The combined seasonal range for heat transport is 0.40 PW. The Florida Straits seasonal cycle possesses a smooth annual periodicity in contrast with previous studies suggesting a more asymmetric structure. No clear evidence is found to support significant changes in the Florida Straits seasonal cycle at sub-decadal periods. Whilst evidence of wind driven Florida Straits transport variability is seen at sub-seasonal and annual periods, a model run from the 1/4° eddy-permitting ocean model NEMO is used to identify an important contribution from internal oceanic variability at sub-annual and interannual periods. The Ekman transport seasonal cycle possesses less symmetric structure, due in part to different seasonal transport regimes east and west of 50 to 60° W. Around 60% of non-seasonal Ekman transport variability occurs in phase section-wide at 26° N and is related to the NAO, whilst Sverdrup transport variability is more difficult to decompose.

Utilizing image texture to detect land-cover change in Mediterranean coastal wetlands - S. Berberoğlu; A. Akin; P. M. Atkinson; P. J. Curran (International Journal of Remote Sensing, 2010)

Geostatistically estimated image noise is a function of variance in the underlying signal - A. Asmat; P. M. Atkinson; G. M. Foody (International Journal of Remote Sensing, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Mapping percentage tree cover from Envisat MERIS data using linear and nonlinear techniques - S. Berberoglu; O. Satir; P. M. Atkinson (International Journal of Remote Sensing, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Estimating per‐pixel thematic uncertainty in remote sensing classifications - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2009)

Modelling geometric and misregistration error in airborne sensor data to enhance change detection - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2007)

Pre-maturity α-amylase and incipient sprouting in UK winter wheat, with special reference to the variety Rialto - A. F. Tjin Wong Joe; R. W. Summers; G. D. Lunn; M. D. Atkinson; P. S. Kettlewell (Euphytica, 2005)

Relationships between airborne fungal spore concentration of Cladosporium and the summer climate at two sites in Britain - P. D. Hollins; P. S. Kettlewell; D. B. Stephenson; J. M. Corden; W. M. Millington; J. Mullins; M. D. Atkinson (International Journal of Biometeorology, 2004)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)